Status Kesehatan Mental Dan Program Kesehatan Mental Anak Sekolah Dasar Di Halmahera Utara - Desi Desi Desi; Meike Yeneka Jacob; Rama Tulus Pilakoannu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Â AbstractMental health is covered with prosperity where retail can cause a bad situation in his life, able to work and able to contribute to society. It is estimated that 20-25% of children experience mental health literature taking into consideration the high prevalence of mental health literature in children, then schools are recommended as for health promotion. The purpose of this research is to know the description of the students ' mental health status and the promotion of mental health in two elementary schools, namely, SD Inpres Meti in Meti Village, East Tobelo Sub District and in SD Inpres, Kusuri village, West Tobelo District in North Halmahera regency. Collection of data using the distribution of the questionnaire by involving students in grades 4-6 and teachers. The questionnaire used was the questionnaires saebers. The results were summarized in 3 categories: disorders of social behavior, symptoms of academic behavior and symptoms of emotional behavior to assess students ' mental health status, while the promotion of mental health on teachers is summarized in six categories: knowledge of Student's mental healthcare promotion, teacher knowledge of student's mental health, school and teacher regulations, learning forms and teaching in the classroom, school relationships with parents and daily behavior of children in schools that often Found. Students of Meti (coastal) elementary school have a risk level of mental health problems of 100% and Studnt of Kusuri (mountain) of 87%, where there is no significant difference.Keywords: Health Promotion, Mental Health Status, Elementary Students